High-frequency genetic transformation of Phalaenopsis amabilis orchid using tomato extract-enriched medium for the pre-culture of protocorms - Semiarti, Endang (2010)
The development of an efficient methodology for the genetic transformation of orchids is needed in order to support the genetic engineering of orchids. It is therefore important to identify those factors affecting the transformation process. Previously, we reported a convenient method for the transformation of Phalaenopsis amabilisusing Agrobacterium tumefaciens, in which intact protocorms were used. We also found that embryos cultured on a medium containing tomato extract grew more rapidly than those cultured on a medium with coconut water. When we used protocorms grown on a medium containing tomato extract, we obtained regenerated shoots that had been transformed with a kanamycin resistance gene at relatively high frequencies (7 – 17%). These results suggest that the rate of growth of pre-cultured protocorms may be important for the successful regeneration of transformed shoots. We also obtained regenerated shoots that had been transformed with the green fluorescent protein (GFP) gene at a high frequency (10 – 14%). Both the presence and expression of these transgenes were confirmed in transformed plants by molecular analyses and by the detection of green fluorescence following excitation with blue light.